PENGARUH HUMAN SKILL TERHADAP KINERJA STAF PENUNJANG MEDIS (INFLUENCE OF HUMAN SKILL TOWARD JOB PERFORMANCE OF MEDICAL SUPPORT STAFF) - Widiarini, Retno (Journal Nursing Care and Biomolecular, 2017)
Medical supporter staffâs performance in Islamic Hospital of Siti Aisyah Madiun inÂ  2016 most got enough value. Counted 45 staffs got enough value with percentage of 61,64% from 73 staffs. Ability of Human Resources represent one ofÂ  factor whichÂ  influencing performance to reach the target of hospital, besides technical ability, ability comprehend others in an organization of vital importance. Human Skill represent ability in have well interaction with working team. This research aim was to know influence of human skill to medical supporter staff performance of Islamic Hospital of Siti Aisyah Madiun in 2017.This research used analytic survey with approach of crossectional. Population in this research were all of medical supporter staffÂ  in Islamic Hospital of Siti Aisyah Madiun counted 73 people. Sample in this research was medical supporter staff counted 42 people. Sampling technique use Purposive Sampling. Data taken by using questionnaire and analyzed by using test of Kendall Tau_b (Ï).Result of this research there was influence of human skill with medical supporter staff performance with value of p-value 0,000 <Î± (0,05) with coefficient correlation 0,612. That can concluded that there was influence ofÂ  human skill to performance with strong influence level.